PLS based quantitative determination of insulin aspart in solution using Raman spectroscopy - Godzo, Hrisanta; Gigopulu, Olga; Brezovska, Katerina; Geshkovski, Nikola; Nakov, Natalija; Acevska, Jelena; Poceva Panovska, Ana; Tonic-Ribarska, Jasmina (Archives of Pharmacy, 2024)
The complex structure of medicines containing polypeptide active substances requires the implementation of challenging analytical approaches, based on physicochemical methods, and, where necessary, biological assays for quality control, as well as for the detection of substandard and falsified products. Vibrational spectroscopic techniques, including Raman spectroscopy, are fast, powerful, and non-destructive techniques which, when combined with multivariate chemometric modelling, can provide specific identification, quantitative determination, and insight into the secondary structure of proteins and peptides. The aim of this study was to investigate the possibility of using Raman spectroscopy as a screening method for quantification of pharmaceutical products containing active substances with polypeptide structures. For that purpose, a model based on partial least square (PLS) analysis for quantitative determination of insulin aspart in solution was developed using Raman spectroscopy. The proposed model enables the establishment of a rapid approach for screening of the quality of formulations containing active substances with polypeptide structure, providing the selection of suspected samples that should be further analysed using routine techniques, which are time-consuming and costly.